2013
DOI: 10.1080/00423114.2013.800215
|View full text |Cite
|
Sign up to set email alerts
|

Tribology of the wheel–rail contact – aspects of wear, particle emission and adhesion

Abstract: The wheel-rail contact is a safety critical interface. Wear, particle emission and adhesion are all wheelrail contact phenomena and are discussed here. All three phenomena are material and system parameters and are linked together. Different countermeasures to one phenomenon such as adhesion enhancement with a friction modifier can increase the wear in the contacting bodies. The wear of railway wheel and rail are linked to the number of airborne particles generated, but the exact number and size distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 76 publications
0
34
0
2
Order By: Relevance
“…From the speed classification point of view, the literature separates wear into mild (removing small fragments of material, often oxide surfaces), heavy, and catastrophic. This classifying separation is shown in (2) as a standard function of sliding (s v ) and a wear factor (w f ) [15]. …”
Section: The Wear Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…From the speed classification point of view, the literature separates wear into mild (removing small fragments of material, often oxide surfaces), heavy, and catastrophic. This classifying separation is shown in (2) as a standard function of sliding (s v ) and a wear factor (w f ) [15]. …”
Section: The Wear Mechanismmentioning
confidence: 99%
“…Figure 5 depicts the damage formation mechanism caused by adhesion at the crystallites boundaries of the metal. The motion of rail vehicles in regular usage can be examined as sources of influence of large dynamic loads of a cyclical nature, which translates to destruction in the form of abrasive and fatigue wear and changes in shape and dimensions of the outer layer [15,22,31].…”
Section: The Wear Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Olofsson et al (2013) found that cyclic loading that leads to wheel surface deformation results in crack nucleation and subsequently removal of material. The excessively worn wheels revealed plastic deformation on the tread that resulted in the initiation of cracks.…”
mentioning
confidence: 99%